Chronically hypertensive transgenic mice expressing human AT1R haplotype-I exhibit increased susceptibility to Francisella tularensis - Ketkar, Harshada; Alqahtani, Maha; Tang, Samantha; Parambath, Sreema Puthiya; Bakshi, Chandra Shekhar; Jain, Sudhir (Frontiers in Microbiology, 2023)
Age-related illnesses, including hypertension and accompanying metabolic disorders, compromise immunity and exacerbate infection-associated fatalities. Renin-angiotensin system (RAS) is the key mechanism that controls blood pressure. Upregulation of RAS through angiotensin receptor type 1 (AT1R), a G-protein coupled receptor, contributes to the pathophysiological consequences leading to vascular remodeling, hypertension, and end-organ damage. Genetic variations that increase the expression of human AT1R may cause the above pathological outcomes associated with hypertension. Previously we have shown that our chronically hypertensive transgenic (TG) mice containing the haplotype-I variant (Hap-I, hypertensive genotype) of human AT1R (hAT1R) gene are more prone to develop the metabolic syndrome-related disorders as compared to the TG mice containing the haplotype-II variant (Hap-II, normotensive genotype). Since aging and an increased risk of hypertension can impact multiple organ systems in a complex manner, including susceptibility to various infections, the current study investigated the susceptibility and potential effect of an acute bacterial infection using a Gram-negative intracellular bacterial pathogen, Francisella tularensis in our hAT1R TG animals. Our results show that compared to Hap-II, F. tularensis-infected aged Hap-I TG mice have significantly higher mortality post-infection, higher bacterial load and lung pathology, elevated inflammatory cytokines and altered gene expression profile favoring hypertension and inflammation. Consistent with worsened phenotype in aged Hap-I mice post-Francisella infection, gene expression profiles from their lungs revealed significantly altered expression of more than 1400 genes. Furthermore, bioinformatics analysis identified genes associated with RAS and IFN-γ pathways regulating blood pressure and inflammation. These studies demonstrate that haplotype-dependent over-expression of the hAT1R gene leads to enhanced susceptibility and lethality due to F. tularensis LVS infection, which gets aggravated in aged animals. Clinically, these findings will help in exploring the role of AT1R-induced hypertension and enhanced susceptibility to infection related respiratory diseases.